2020
DOI: 10.1161/jaha.120.016504
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐percutaneous Coronary Intervention Pericoronary Adipose Tissue Attenuation Evaluated by Computed Tomography Predicts Global Coronary Flow Reserve After Urgent Revascularization in Patients With Non–ST‐Segment–Elevation Acute Coronary Syndrome

Abstract: Background Impaired global coronary flow reserve (g‐CFR) is related to worse outcomes. Inflammation has been postulated to play a role in atherosclerosis. This study aimed to evaluate the relationship between pre‐procedural pericoronary adipose tissue inflammation and g‐CFR after the urgent percutaneous coronary intervention in patients with first non–ST‐segment–elevation acute coronary syndrome. Methods and Results Phase‐contrast cine‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Macrophages in the PvAT were previously associated with an increased risk of thrombosis in human coronary arteries. 13 Greater PvAT attenuation, which is a marker of PvAT inflammation in imaging exams, was independently associated with poorer global coronary reserve flow 1 month after an acute coronary event, 36 higher acute coronary syndrome, 37 and increased cardiac death. 38 Our stratified analyses demonstrated that the inflammation mediated by M1 macrophages in the periplaque PvAT was associated with characteristics of plaque progression and destabilization in thrombosed coronary arteries, suggesting that M1 macrophages in the PvAT might influence the inflammation in acute coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages in the PvAT were previously associated with an increased risk of thrombosis in human coronary arteries. 13 Greater PvAT attenuation, which is a marker of PvAT inflammation in imaging exams, was independently associated with poorer global coronary reserve flow 1 month after an acute coronary event, 36 higher acute coronary syndrome, 37 and increased cardiac death. 38 Our stratified analyses demonstrated that the inflammation mediated by M1 macrophages in the periplaque PvAT was associated with characteristics of plaque progression and destabilization in thrombosed coronary arteries, suggesting that M1 macrophages in the PvAT might influence the inflammation in acute coronary events.…”
Section: Discussionmentioning
confidence: 99%
“…ese cytokines can regulate energy balance and hormone metabolism [18]. In the study of Kanaji et al (2020) [19], it was found that patients with non-ST-segment elevation ACS undergoing percutaneous coronary intervention for one month were related to ADP and coronary artery blood flow reserve (g-CFR) impairment. In the g-CFR impaired group, there were remarkable differences in the location of the crime lesion, the level of amino-terminal B-type natriuretic peptide precursor, the level of high-sensitivity c-reactive protein (hs-CRP), and the ADP around the coronary arteries.…”
Section: Hemodynamics Of Vulnerable Plaquesmentioning
confidence: 99%
“…1 ). Fourteen studies presented two populations each [ 9 , 11 , 15 17 , 23 , 25 , 27 , 29 , 31 , 32 , 34 , 47 , 49 ], while two studies presented four populations each [ 30 , 35 ]. Therefore, a total of 67 independent populations were included.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a total of 67 independent populations were included. Among the 47 studies, 22 were from Japan [ 19 21 , 23 37 , 42 , 44 , 45 , 47 ], eight from the United States [ 7 , 14 , 22 , 40 , 41 , 48 , 51 , 55 ], five from Sweden [ 12 , 16 , 17 , 53 , 54 ], three from Germany and Sweden [ 11 , 15 , 46 ], two from Finland [ 38 , 39 ], and one each from Australia [ 18 ], France [ 43 ], Italy [ 9 ], Norway [ 13 ], Turkey [ 10 ], the United Kingdom [ 49 ], Switzerland [ 7 ], and the Netherlands [ 50 ]. Year of publication ranged from 1992 to 2022.…”
Section: Resultsmentioning
confidence: 99%